From employee to entrepreneur: The role of unemployment risk - Hou, Ai Jun; Jonsson, Sara; Li, Xiaoyang; Ouyang, Qinglin (Journal of Financial Economics, 2025)
We use Swedish administrative data to study the role of unemployment risk in salaried employees’ decisions to become entrepreneurs. Using the 2001 relaxation of Sweden’s last-in-first-out (LIFO) dismissal rule as an exogenous shock to unemployment risk, we find that employees facing increased unemployment risk are more likely to become entrepreneurs. The effect is more pronounced for employees with longer tenure, as they were newly exposed to greater unemployment risk. When we track entrepreneurs’ income dynamics and the performance of their ventures, we find that entrepreneurs who used to face greater unemployment risk do not underperform compared to other entrepreneurs. Our results provide some of the first empirical evidence of how employees respond to increased unemployment risk.